The Paradigm Shift of Wali Mujbir in Islamic Jurisprudence Following Law No. 12 of 2022 on Sexual Violence Crimes in the Banda Aceh Office of Religious Affairs - Innaki Rahmah Salsabiela; Yuni Roslaili; Nufiar Nufiar; Farhan Nurhadi (Prodi Magister Ilmu Agama Islam, Pascasarjana UIN Ar-Raniry, 2025)
The shift in the meaning and position of the wali mujbir in the marriage of daughters in Indonesia has become an interesting issue to analyze following the enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes. In classical Islamic law, a wali mujbir holds full authority to marry off his daughter without her consent. However, this new regulation, through Article 10 of the Sexual Violence Crimes Law, imposes limitations and criminal sanctions on forced child marriages. This study aims to analyze the position of wali mujbir under Islamic law and Indonesian marriage regulations, the shift in meaning and status of wali mujbir post-enactment of Law Number 12 of 2022, its implementation in the Religious Affairs Offices (KUA), and the maslahah (public interest) values ​​in the UU TPKS regarding child marriage. The research employs normative and empirical/sociological legal methods, using a conceptual and qualitative approach. The data were analyzed qualitatively. The findings reveal that while the concept of wali mujbir in Isla The Minister of Religious Affairs should strictly regulate interview procedures to detect potential coercion by the wali. The government is advised to revise the Marriage Law to explicitly prohibit forced marriage and align it with the TPKS Law and the Child Protection Law. KUA officers should receive gender-sensitive training and be required to provide a private, safe space for prospective brides to express objections without family or guardian pressure.